Review of the genus Pogonolaelaps Nemati & Gwiazdowicz (Acari: Laelapidae), with description of a new species from Iran - Joharchi, Omid; Ramroodi, Sara; Halliday, Bruce (Zootaxa, 2020)
We describe a new species, Pogonolaelaps termitophilus sp. nov., from specimens collected from termite nests in Iran. We clarify the identity of the genus Pogonolaelaps Nemati & Gwiazdowicz, 2016, its type species Laelaps canestrinii Berlese, 1892, and the related genus Laelaspisella Marais & Loots, 1969.